The marriage of Bette and Boo - Durang, Christopher 1949- (Nelson Doubleday, Inc., 1985)
Never have marriage and the family been more scathingly or hilariously savaged than in this brilliant black comedy. The marriage of Bette and Boo brings together two of the maddest families in creation in a portrait album of family life?s uncertainties and confusion. Bereaved by miscarriages, undermined by their families, separated by alcoholism, assaulted by disease, and mystified by their priest, Bette and Boo, in their bewildered attempts to provide a semblance of hearth and home, are presented with a poignant compassion that enriches and enlarges the play, and places Christopher Durang squarely in the forefront of American dramatists.